Analysis of Company Performance Through a Management Control System Approach: A Study of Financial Services Authority Documents in 2019 - Nadia Raudatul Hasanah; Bunga Rismawati; Raudya Nida Hanifah; Salsabila Putri Kusnaedi; Tiolina Evi Nausta Pardede (Manunggal Halim Jaya, 2026)
This study analyzes the organizational performance of Indonesia's Financial Services Authority (OJK) in 2019 from the perspective of the Management Control System. Drawing on a document analysis of the OJK 2019 Performance Report, the research evaluates the effectiveness of the integration of strategy, budget, and performance through the Management, Strategy, Budget, and Performance System (MSAK), which is rooted in the Balanced Scorecard (BSC) framework. The findings indicate that OJK's Management Control System successfully maintained financial sector stability amidst global economic slowdown. External performance indicators remain robust, with banking credit growth reaching 7.05% (YoY) and the net Non-Performing Loan (NPL ratio) contained at a healthy 1.20%. Furthermore, foreign investors recorded a net buy of IDR 49.2 trillion in the capital market. Internally, OJK significantly strengthened its control mechanisms by implementing Integrated Governance, Risk, and Compliance (GRC) and using Supervisory Technology (SupTech) such as OJK-BOX and Continuous Audit Continuous Monitoring (CACM). This control environment resulted in the organization achieving an Unqualified Opinion on its financial statements. The study concludes that OJK's successful performance relied on an adaptive, risk-based Management Control System that strategically leveraged digital transformation.